The Basic Principles of External Skeletal Fixation Using the Ilizarov and Other Devices - Solomin, Leonid; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2012)
When it was developed, the Ilizarov device represented a revolutionary advance that made it possible to correct previously untreatable conditions through the stimulation of bone growth based on the principle of distraction osteogenesis. The device subsequently gained popularity among surgeons throughout the world since it can be used for the treatment of fractures that have failed to heal satisfactorily and for deformity correction. The technique is, however, complex and requires specialist knowledge if it is to be applied optimally.This is the second edition of a well-received book that focuses primarily on external fixation using the Ilizarov device but also considers other devices employed for the purpose. The opening chapters include discussion of biomechanical principles, use of a system of coordinates to allow safer insertion of K-wires and half pins, preoperative preparation, and principles of frame construction. External fixation of a variety of fractures in different pathologic settings is then clearly explained in a series of detailed chapters with the aid of high-quality illustrations. Numerous case reports are included to illustrate the results of different treatment methods. In addition, principles of postoperative management are described and advice is provided on correction of errors and treatment of complications. Since the first edition the text has been thoroughly updated, with inclusion of contributions from leading world experts. This volume will serve as an indispensable manual both for trainee orthopedic surgeons embarking on a steep learning curve and for more experienced surgeons requiring advice and guidance in demanding cases.
Part 1 General Aspects of External Fixation -- Part 2 Specific Aspects of External Fixation -- Part 3 Supplementary materials.
Keywords: Medicine; Orthopedics; Orthopedic surgery; Rehabilitation; Endoscopic surgery; Trauma; Medicine & Public Health; Orthopedics; Surgical Orthopedics; Rehabilitation Medicine; Minimally Invasive Surgery; Traumatic Surgery